"Inte förrän en kollega blir skjuten och dör. Det är först då det kommer bli ett jävla liv." : en kvalitativ intervjustudie om kriminaljournalisters yrkeserfarenheter av hot och hat - Frydenlund,Andrea; Stinnerbom,Jacqueline (2024)
The purpose of our study is to investigate how eight crime journalists experience their professional life, and whether their professional choice affects their private life. We want to see how our respondents are affected by threats and harassment. We also want to see what support is available when this happens. Furthermore, we also want to investigate what kind of ethical dilemmas they have faced in connection with their professional practice. This study is conducted using qualitative interviews with thematic categories. The theoretical concepts we started from are: role theory, coping, chilling effect, and press and professional ethics. The main results we obtained are that all crime journalists have been affected in some way by hate or threats due to their choice of profession. The results also showed that our respondents used several different strategies in their work, in order to dare to carry out the work and reduce stress. Crime journalists are also faced with many ethical dilemmas during their work, where it is not clear what is right or wrong.